A Cornflower Extract Containing N-Feruloylserotonin Reduces Inflammation in Human Skin by Neutralizing CCL17 and CCL22 and Inhibiting COX-2 and 5-LOX. (13th September 2021) - Carola, Christophe; Salazar, Andrew; Rakers, Christin; Himbert, Franck; Do, Quoc-Tuan; Bernard, Philippe; von Hagen, Joerg
Abstract : Thymus and Activation-Regulated Chemokine (TARC/CCL17) and Macrophage-Derived Chemokine (MDC/CCL22) are two key chemokines exerting their biological effect via binding and activating a common receptor CCR4, expressed at the surface of type 2 helper T (Th2) cells. By recruiting Th2 cells in the dermis, CCL17 and CCL22 promote the development of inflammation in atopic skin. The aim of this research was to develop a plant extract whose biological properties, when applied topically, could be beneficial for people with atopic-prone skin. The strategy which was followed consisted in identifying ligands able to neutralize the biological activity of CCL17 and CCL22. Thus, an in silico molecular modeling and a generic screening assay were developed to screen natural molecules binding and blocking these two chemokines. N -Feruloylserotonin was identified as a neutraligand of CCL22 in these experiments. A cornflower extract containing N -feruloylserotonin was selected for further in vitro tests: the gene expression modulation of inflammation biomarkers induced by CCL17 or CCL22 in the presence or absence of this extract was assessed in the HaCaT keratinocyte cell line. Additionally, the same cornflower extract in another vehicle was evaluated in parallel with N -feruloylserotonin for cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LOX) enzymatic cellular inhibition. The cornflower extract was shown to neutralize the two chemokines in vitro, inhibited COX-2 and 5-LOX, and demonstrated anti-inflammatory activities due mainly to the presence of N -feruloylserotonin. Although these findings would need to be confirmed in an in vivo study, the in vitro studies lay the foundation to explain the benefits of the cornflower extract when applied topically to individuals with atopic-prone skin.